Efeitos da história térmica nas propriedades do polímero pet: Um experimento para ensino de análise térmica - Bannach, Gilbert [UNESP]; Perpétuo, Glauco Lini [UNESP]; Cavalheiro, Éder Tadeu Gomes; Cavalheiro, Carla Cristina Schmitt; Rocha, Rafael Rodrigo (My University, 2011)
Polyethilenetherephtalate (PET) is commonly used in manufacturing of beverage bottles representing a didactic appeal in thermal analysis education due to its presence in the student's day life. Additionally such polymer presents well defined thermal analytical curves and a well known thermal behavior. TGA curve is used to present the thermal stability. The thermal history effects in the thermal properties of a PET sample from a soft drink bottle are used to demonstrate the effect of different heating/cooling conditions on glass transition, melting, crystallization and crystalline degree using DSC curves.
Effects of the thermal history on thermal properties of polymers: An experiment for thermal analysis education
Keywords: PET; Polymers; Thermal analysis education